The Effect of Differentiated Instruction on Fourth-Grade Students’ Learning Outcomes in Pancasila Education at SD Inpres 3 Talise - Riska A. Pipiot; Arif Firmansyah; Muchdar Muchdar; Herlina Herlina; Muhammad Nazimuddin Al Kamil (FKIP - Universitas Riau, 2026)
Low student learning outcomes in Pancasila Education remain a challenge in elementary schools due to learning processes that have not fully accommodated differences in students’ readiness, interests, and learning profiles. Preliminary observations conducted in Grade IV of SD Inpres 3 Talise revealed that 18 out of 31 students had not achieved the Minimum Learning Mastery Criteria (KKM). Therefore, an instructional approach that addresses diverse learning needs is required. This study aimed to determine the effect of the differentiated instruction approach on students’ learning outcomes in Pancasila Education. The study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 31 Grade IV students selected through a saturated sampling technique. Data were collected using multiple-choice pretest and posttest instruments and analyzed through validity, reliability, and normality tests, followed by the Wilcoxon Signed-Rank test using SPSS version 25. The findings showed a substantial improvement in students’ learning outcomes, with the average score increasing from 54.42 on the pretest to 89.48 on the posttest. The hypothesis test yielded a significance value of <0.001 (<0.05), indicating that the differentiated instruction approach had a significant positive effect on students’ learning outcomes in Pancasila Education.